2001
DOI: 10.1128/aem.67.9.4215-4224.2001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Population Structures in Soil Particle Size Fractions of a Long-Term Fertilizer Field Experiment

Abstract: Soil structure depends on the association between mineral soil particles (sand, silt, and clay) and organic matter, in which aggregates of different size and stability are formed. Although the chemistry of organic materials, total microbial biomass, and different enzyme activities in different soil particle size fractions have been well studied, little information is available on the structure of microbial populations in microhabitats. In this study, topsoil samples of different fertilizer treatments of a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
352
5
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(402 citation statements)
references
References 59 publications
27
352
5
18
Order By: Relevance
“…Girvan et al (2003) reported that soil type and its properties could be a dominant factor controlling the general microbial community composition. Soil total bacterial community composition could be more associated to the particle size fraction than the different organic amendments (Sessitsch et al 2001). Another possible reason for interpreting this surprising result could be that during long-term (16 years) applications of organic fertilizers, the soil bacterial population would have shifted so that those species capable of using such fertilizers would thrive while some other species would have died out, thus leading to a less diverse population.…”
Section: Discussionmentioning
confidence: 92%
“…Girvan et al (2003) reported that soil type and its properties could be a dominant factor controlling the general microbial community composition. Soil total bacterial community composition could be more associated to the particle size fraction than the different organic amendments (Sessitsch et al 2001). Another possible reason for interpreting this surprising result could be that during long-term (16 years) applications of organic fertilizers, the soil bacterial population would have shifted so that those species capable of using such fertilizers would thrive while some other species would have died out, thus leading to a less diverse population.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of dominant bacterial groups related to particle size, bacteria belonging to the phylum Acidobacteria and the genus Prosthecobacter sp. (phylum Verrucomicrobia) were found to be more diverse in soils with small particles, whereas α-Proteobacteria dominated in large particle soils (Sessitsch et al 2001). In addition, the availabilities of nutrients and organic matter also strongly influence bacterial abundances and diversities (Smit et al 2001;Hartman et al 2008;Will et al 2001;Han et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent studies have shown relations between microbes and environmental factors, such as geographical location (Fierer and Jackson 2006;Lauber et al 2009), soil texture (Sessitsch et al 2001), land use (Smit et al 2001;Cookson et al 2007;Brons and van Elsas 2008;Hartman et al 2008;Will et al 2001), pH (Fierer and Jackson 2006;Lauber et al 2009;Hartman et al 2008), nutrients (Cookson et al 2007;Will et al 2001;Han et al 2008), contaminants like oil (Liang et al 2011), and heavy metals (Sandaa et al 2001;Kelly et al 1999;Roane and Pepper 2000;Lee et al 2008). Of the abovementioned factors, pH is regarded one of the most important in terms of shaping biogeographical patterns (Fierer and Jackson 2006;Lauber et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In detailed studies community phyla structures also prove to be seasonally dynamic and highly heterogenous even in homogeneous landscapes (Axelrood et al, 2002;Franklin and Mills, 2003;Sliwinski and Goodman, 2004). A few studies have attempted to correlate community structure to ecological parameters (Sessitsch et al, 2001;Fierer and Jackson 2006;Fierer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%